New opportunities for experiments in fluvial geomorphology: the flume PTETHYS - Pirkhoffer, Ervin; Halmai, Ákos; Czigány, Szabolcs; Bugya, Titusz; Rábay, Andor; Bötkös, Tamás; Nagy, Gábor; Balassa, Bettina; Jancskárné AnweilerIldikó; Lóczy, Dénes (Hungarian Geographical Bulletin, 2014)
In recent decades both physical modelling and computer simulation of fluvial processes has undergone rapid progress. The paper summarizes the achievements of both international and Hungarian laboratory experiments in fluvial geomorphology. Then the new automatically governed flume facility, called PTETHYS (Project for Tectonical and Hydrological Simulations) recently set up at the Faculty of Natural Sciences, University of Pécs, is presented and some of the new opportunities it offers for research in fluvial geomorphology are briefly demonstrated: the identification of geomorphological thresholds; modelling the generation of (flash) floods and its application for the reconstruction of the architectural elements and geomorphic evolution of floodplains. Some important channel parameters can be quantitatively investigated: channel cross-section change, amount of bedload influencing braiding, current velocity distribution etc. The novelty of the facility is the easy adjustment of channel slope and continuous experimenting (no need for interruption as in the case of laserscanned experiments). The scaling necessary for quantitative analyses is also tackled.